Social Support from Neighbourhood Unit (RT) Leaders for Families of Covid-19 Patients in Sumbersari Subdistrict, Sumbersari District, Jember Regency - Zilvi Fuadiyah Nur; A. Haikal Fikri Imas (Pro-Life, 2025)
COVID-19 has significantly affected Indonesia, including East Java and Jember Regency, resulting in high case rates and widespread psychological distress. Social support from RT leaders plays a crucial role in reducing stress, improving mental well-being, strengthening family resilience, and helping prevent transmission through educational, emotional, instrumental, informational, and appraisal support. This study was conducted because research on RT leaders' social support for families of COVID-19 patients and its psychological impact remains largely unexplored. The objective of this study was to analyze the social support provided by RT leaders to families affected by COVID-19. A qualitative design with a phenomenological approach was employed, involving five primary informants and five additional informants through in-depth interviews. The study was conducted from March to November 2021 in Sumbersari Village, Sumbersari District, Jember Regency. The findings of this study revealed that RT leaders played a significant role in providing informational, emotional, instrumental, and appraisal support to the families of COVID-19 patients. Such support enhanced motivation, facilitated recovery, and strengthened psychosocial resilience within the community. This research is expected to enhance families affected by COVID-19's understanding of the social support provided by RT leaders, so that both COVID-19 patients and those with other illnesses may be encouraged to improve their quality of life, particularly their health.